Metgas Production from Bi-reforming of Methane over La-modified Santa Barbara Amorphous-15 Supported Nickel Catalyst - Singh, Sharanjit; Nga, Nguyen Thi Anh; Pham, Thong L. M.; Tan, Ji Siang; Phuong, Pham T. T.; Khan, Maksudur R.; Vo, Dai-Viet N. (AIDIC, 2017)
An integrated process of steam reforming coupled with CO2 reforming of methane (bi-reforming) has emerged as a promising reforming technique among pre-existing technologies. Syngas with a H2/CO ratio of about 2 (called Metgas) is desirable for the production of methanol and liquid hydrocarbons. La-modified and unmodified Santa Barbara Amorphous-15 (SBA-15) supports were synthesised by one-pot and hydrothermal techniques. These supports were further impregnated with Ni(NO3)2 metal precursor solution using an incipient wetness impregnation method. The methane bi-reforming reaction was carried out in a tubular fixedbed quartz reactor under atmospheric pressure at varying temperature of 1,023 - 1,073 K with CH4/H2O/CO2 = 3/2/1 and gas hourly space velocity (GHSV) of 36 L gcat-1 h-1. The physicochemical properties of both catalysts were scrutinised by BET, X-ray diffraction (XRD) and H2 temperature-programmed reduction (H2-TPR). The BET results showed that La-modified SBA-15 support possessed higher surface area of 737 m2 g-1 in comparison with the unmodified SBA-15 support counterpart (669 m2 g-1). An inevitable decline in surface area was observed after NiO addition for both supports due to the successful diffusion of NiO particles into the mesoporous channels of supports. XRD measurements confirmed the presence of NiO and amorphous SiO2 phases for both 10 % Ni/La-SBA-15 and 10 % Ni/SBA-15 catalysts. No characteristic peaks were detected for La2O3 phase reasonably owing to the incorporation of La2O3 into the framework of SBA-15 support. Both reactant conversions and gaseous product yields improved considerably with an increase in reaction temperature for both catalysts. A desirable H2/CO ratio of about 2 was achieved at reaction temperature of 1,048 - 1,073 K. La-modified SBA-15 supported Ni catalyst exhibited greater activity and selectivity than those of unmodified counterpart.